Pineapple guava [Acca sellowiana (O.Berg) Burret] growth, production and fruit quality in response to potassium nitrate, potassium phosphate and ethephon - Combariza, Luis Fernando; Neira, César Augusto; Fischer, Gerhard; Corredor, Guillermo; Quintero, Ómar Camilo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
In La Vega (Cundinamarca, Colombia; 2,350 m above sea level, 17°C average temperature, 85% relative humidity, and 1,423 mm annual precipitation), the effect of three chemical products, used for floral induction, on 6 yearold pineapple guava trees (‘Clone 41’ or ‘Quimba’) were studied. The applied chemical agents were the foliar fertilizers KNO3 (potassium nitrate 13-0-46® 1%, 1.5%, 2%), KH2PO4 (potassium phosphate; Cosmofoliar 0-32- 43®; 0.5%, 0.75%, 1.0%), and ethephon (Ethrel® 48 SL; 100, 150, 200 mg·L-1) their effects were evaluated during fruit development, until physiological maturity, determining fruit production and quality. Regarding the longitudinal and cross-sectional size of the fruit, KH2PO4 at 0.5%, followed by the 100 mg·L-1 ethephon treatment, responded better compared to the other treatments, with an optimal production of fruits of exportable quality. Similarly, 0.5% KH2PO4 produced the highest number of set and harvested fruits. Ethephon at 100 mg·L-1 tended to originate the greatest fresh weight fruits. The applied products did not present any alteration in their chemical variables (pH, total soluble solids and total titratable acidity) of harvested fruits.